---------------------------------------------------------------------------------------------------- --- Copyright (c) 2014 Parikshit Khanna. All rights reserved. --- Released under Apache 2.0 license as described in the file LICENSE. --- Authors: Parikshit Khanna, Jeremy Avigad ---------------------------------------------------------------------------------------------------- -- Theory list -- =========== -- -- Basic properties of lists. import logic data.nat -- import congr open nat -- open congr open eq.ops eq inductive list (T : Type) : Type := nil {} : list T, cons : T → list T → list T definition refl := @eq.refl namespace list -- Type -- ---- infixr `::` := cons section variable {T : Type} theorem list_induction_on {P : list T → Prop} (l : list T) (Hnil : P nil) (Hind : forall x : T, forall l : list T, forall H : P l, P (cons x l)) : P l := list.rec Hnil Hind l theorem list_cases_on {P : list T → Prop} (l : list T) (Hnil : P nil) (Hcons : forall x : T, forall l : list T, P (cons x l)) : P l := list_induction_on l Hnil (take x l IH, Hcons x l) notation `[` l:(foldr `,` (h t, cons h t) nil) `]` := l -- Concat -- ------ definition concat (s t : list T) : list T := list.rec t (fun x : T, fun l : list T, fun u : list T, cons x u) s infixl `++` := concat theorem nil_concat (t : list T) : nil ++ t = t := refl _ theorem cons_concat (x : T) (s t : list T) : (x :: s) ++ t = x :: (s ++ t) := refl _ theorem concat_nil (t : list T) : t ++ nil = t := list_induction_on t (refl _) (take (x : T) (l : list T) (H : concat l nil = l), H ▸ (refl (cons x (concat l nil)))) theorem concat_nil2 (t : list T) : t ++ nil = t := list_induction_on t (refl _) (take (x : T) (l : list T) (H : concat l nil = l), -- H ▸ (refl (cons x (concat l nil)))) H ▸ (refl (concat (cons x l) nil))) theorem concat_assoc (s t u : list T) : s ++ t ++ u = s ++ (t ++ u) := list_induction_on s (refl _) (take x l, assume H : concat (concat l t) u = concat l (concat t u), H ▸ refl _) theorem concat_assoc2 (s t u : list T) : s ++ t ++ u = s ++ (t ++ u) := list_induction_on s (refl _) (take x l, assume H : concat (concat l t) u = concat l (concat t u), calc concat (concat (cons x l) t) u = cons x (concat (concat l t) u) : refl _ ... = concat (cons x l) (concat t u) : { H }) theorem concat_assoc3 (s t u : list T) : s ++ t ++ u = s ++ (t ++ u) := list_induction_on s (refl _) (take x l, assume H : concat (concat l t) u = concat l (concat t u), calc concat (concat (cons x l) t) u = cons x (concat l (concat t u)) : { H } ... = concat (cons x l) (concat t u) : refl _) theorem concat_assoc4 (s t u : list T) : s ++ t ++ u = s ++ (t ++ u) := list_induction_on s (refl _) (take x l, assume H : concat (concat l t) u = concat l (concat t u), calc concat (concat (cons x l) t) u = cons x (concat (concat l t) u) : refl _ ... = cons x (concat l (concat t u)) : { H } ... = concat (cons x l) (concat t u) : refl _) -- Length -- ------ definition length : list T → ℕ := list.rec 0 (fun x l m, succ m) -- TODO: cannot replace zero by 0 theorem length_nil : length (@nil T) = zero := refl _ theorem length_cons (x : T) (t : list T) : length (x :: t) = succ (length t) := refl _ theorem length_concat (s t : list T) : length (s ++ t) = length s + length t := list_induction_on s (calc length (concat nil t) = length t : refl _ ... = 0 + length t : {symm !zero_add} ... = length (@nil T) + length t : refl _) (take x s, assume H : length (concat s t) = length s + length t, calc length (concat (cons x s) t ) = succ (length (concat s t)) : refl _ ... = succ (length s + length t) : { H } ... = succ (length s) + length t : {symm !add.succ_left} ... = length (cons x s) + length t : refl _) -- Reverse -- ------- definition reverse : list T → list T := list.rec nil (fun x l r, r ++ [x]) theorem reverse_nil : reverse (@nil T) = nil := refl _ theorem reverse_cons (x : T) (l : list T) : reverse (x :: l) = (reverse l) ++ (cons x nil) := refl _ -- opaque_hint (hiding reverse) theorem reverse_concat (s t : list T) : reverse (s ++ t) = (reverse t) ++ (reverse s) := list_induction_on s (calc reverse (concat nil t) = reverse t : { nil_concat _ } ... = concat (reverse t) nil : symm (concat_nil _) ... = concat (reverse t) (reverse nil) : {symm (reverse_nil)}) (take x l, assume H : reverse (concat l t) = concat (reverse t) (reverse l), calc reverse (concat (cons x l) t) = concat (reverse (concat l t)) (cons x nil) : refl _ ... = concat (concat (reverse t) (reverse l)) (cons x nil) : { H } ... = concat (reverse t) (concat (reverse l) (cons x nil)) : concat_assoc _ _ _ ... = concat (reverse t) (reverse (cons x l)) : refl _) -- -- add_rewrite length_nil length_cons theorem reverse_reverse (l : list T) : reverse (reverse l) = l := list_induction_on l (refl _) (take x l', assume H: reverse (reverse l') = l', show reverse (reverse (cons x l')) = cons x l', from calc reverse (reverse (cons x l')) = concat (reverse (cons x nil)) (reverse (reverse l')) : {reverse_concat _ _} ... = cons x l' : {H}) -- Append -- ------ -- TODO: define reverse from append definition append (x : T) : list T → list T := list.rec (x :: nil) (fun y l l', y :: l') theorem append_nil (x : T) : append x nil = [x] := refl _ theorem append_cons (x : T) (y : T) (l : list T) : append x (y :: l) = y :: (append x l) := refl _ theorem append_eq_concat (x : T) (l : list T) : append x l = l ++ [x] := list_induction_on l (refl _) (take y l, assume P : append x l = concat l [x], P ▸ refl _) theorem append_eq_reverse_cons (x : T) (l : list T) : append x l = reverse (x :: reverse l) := list_induction_on l (calc append x nil = [x] : (refl _) ... = concat nil [x] : {symm (nil_concat _)} ... = concat (reverse nil) [x] : {symm (reverse_nil)} ... = reverse [x] : {symm (reverse_cons _ _)} ... = reverse (x :: (reverse nil)) : {symm (reverse_nil)}) (take y l', assume H : append x l' = reverse (x :: reverse l'), calc append x (y :: l') = (y :: l') ++ [ x ] : append_eq_concat _ _ ... = concat (reverse (reverse (y :: l'))) [ x ] : {symm (reverse_reverse _)} ... = reverse (x :: (reverse (y :: l'))) : refl _) end end list